Mortality of acute mesenteric ischemia remains unchanged despite significant increase in utilization of endovascular techniques. (February 2016) - Eslami, Mohammad H; Rybin, Denis; Doros, Gheorghe; McPhee, James T; Farber, Alik
Introduction: In this study, we evaluated if increase in utilization of endovascular surgery has affected in-hospital mortality rates among patients with acute mesenteric ischemia. Methods: The National Inpatient Sample (2003–2011) was queried for acute mesenteric ischemia using ICD-9 code for acute mesenteric ischemia (557.1). This cohort was divided into patients treated with open vascular surgery (open vascular group) and by endovascular therapies (endovascular group) based on the ICD-9CM procedure codes. Multivariable logistic regression was used to determine temporal trend for mortality while adjusting for confounding variables. Results: There was 1.45-fold increase in utilization of endovascular techniques in this study. In-hospital mortality rate, total median charges and length of stay were significantly lower among the endovascular group than the open vascular group despite having significantly higher Elixhauser comorbidities index (3 ± 0.1 vs. 2.7 ± 0.1, p = .003). Over the course of the study period, there was no change in the overall mortality rate despite higher endovascular utilization. Factors associated with increased mortality included age, open surgical repair (Odds ratio: 1.45, 95% Confidence Interval: 1.10–1.91, p = .016) and bowel resection Odds ratio: 2.88, 95% Confidence Interval: 2.01–4.12). Conclusion: The mortality rate for acute mesenteric ischemia remains unchanged throughout this contemporary study. Open surgical intervention, bowel resection and age were associated with increased mortality. Endovascular group patients had better survival despite higher morbidity indices.